THE INFLUENCE OF ETHNOMATHEMATICS-BASED REALISTIC MATHEMATICS LEARNING ON COMPREHENSION ABILITY MATHEMATICS CONCEPTS OF SMP/MTs STUDENTS - Ulfa Fajrina; Lukman Ibrahim; Muhammad Yani (Prodi Tadris Matematika Universitas Muhammadiyah Aceh, 2022)
This study aims to determine the effect of realistic mathematics learning based on ethomathematics and conventional learning on the ability to understand mathematical concepts of junior high school students. The research method use is quasi experiment, with a pretest-posttest control group design. The population in this study were all students of class VII MTsS Darussaadah Cot Tarom, while the sampling was carried out using simple random sampling (by just randomizing the classes) so that class VII.1 was selected as the experiment class using realistic mathematics learning based on etnomathematics and class VII.2 as a control class using conventional learning. Data collection used a test sheet for understanding mathematical concepts which was then analyzed using an independent sample t-test via SPSS. The reserch results obtained that the velue of sig (2-tailed) independent sample t-test 0.0000.05. so that H0 is rejected and H1 is accepted, it can be concluded that the ability to understand mathematical concepts taught using etnomathematical-based realistic mathematical learning is better that the ability to understand mathematical concepts taught using conventional learning. The above conclusions are supported by the fact that during the learning process using realistic mathematics based on ethnomathematical associated whith local culture can increase understanding of awareness and attractiveness so as to increase students understanding of the benefits and concepts of mathematics in everyday life.Keywords: Realistic mathematics learning, Ability undertstanding of mathematical concepts, Ethnomathematics Banda Aceh..